2016
DOI: 10.1590/0034-7167.2016690103i
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de ações ecologicamente sustentáveis no processo de medicação

Abstract: Objective: to analyze sustainable actions from an environmental point of view in the medication process, from the reception of the prescription of the pharmacy to waste discard by nursing. Method: study before and after performed through Lean Six Sigma methodology. The sample consisted of the amount and type of waste resulting from the pharmacy and nursing services of a medical-surgical clinical unit. Results: after the intervention was obtained at the pharmacy a reduction of 74.8% of chemical, infectious and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 12 publications
0
25
0
12
Order By: Relevance
“…O serviço de farmácia hospitalar foi um dos setores analisados, com o objetivo de melhorar a gestão de estoques. O segundo estudo brasileiro identificado (Furukawa et al, 2016) analisou, pela metodologia Lean Seis Sigma, ações sustentáveis do ponto de vista ambiental em processos relacionados a medicamentos no contexto hospitalar, desde o recebimen-to da prescrição pela Farmácia Hospitalar até o descarte dos resíduos pelos enfermeiros, uma vez que os medicamentos são administrados.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O serviço de farmácia hospitalar foi um dos setores analisados, com o objetivo de melhorar a gestão de estoques. O segundo estudo brasileiro identificado (Furukawa et al, 2016) analisou, pela metodologia Lean Seis Sigma, ações sustentáveis do ponto de vista ambiental em processos relacionados a medicamentos no contexto hospitalar, desde o recebimen-to da prescrição pela Farmácia Hospitalar até o descarte dos resíduos pelos enfermeiros, uma vez que os medicamentos são administrados.…”
Section: Resultsunclassified
“…Também foi verificada uma abordagem mais alinhada com a sustentabilidade ambiental, com todo o processo de análise de medicamentos, desde a recepção da receita pela Farmácia Hospitalar até a disposição dos resíduos pelos enfermeiros, com foco na gestão de resíduos. Como resultado, foi alcançada uma redução na quantidade de resíduos químicos, infecciosos, perfurantes e de corte gerados, além de um aumento na quantidade de resíduos comuns e recicláveis (Furukawa et al, 2016).…”
Section: Classificação De Artigosunclassified
“…Findings have revealed that a combination of green, lean, and six sigma tools would bring more benefits as compared to tools from an individual approach, however, very few articles have integrated these tools for a combined effect [11,45,[87][88][89].…”
Section: Enablers Of Glss Approachmentioning
confidence: 99%
“…Thus, they must complement each other and the LSS is method by which hospitals can control costs, reduce the likelihood of errors and improve patient safety and health care quality, promoting sustainability practices yields not only environmental benefits, but also economic ones for the institution. Furukawa, Cunha, and Pedreira (2016) Based on the above implications, it was shown that there is a need for more holistic approaches aligning Lean, Six Sigma key concepts and tools with green practices. From the literature review, it was discovered that by integrating Green and Lean/LSS in service processes it will facilitate the organization in managing and assuring customer needs, dealing with qualities and strategies, and considering the welfare of all stakeholders, thus improving the TBL performance in an integrated way.…”
Section: Logisticsmentioning
confidence: 99%